Wavelet based flickermeter - Guntupalli Ignatius Marien Sanjay. (2008)
Wavelet Transform has been touted as an excellent signal processing technique for analyzing time-varying signal. It is challenging the well known Fourier-based technique, which is generally regarded as only suitable for stationary signal. Varying loads such as arc-furnaces and welding operations usually cause voltage fluctuation that leads to light flickering. As a result, the voltage magnitude will vary constantly and it appears that Wavelet Transform would be an ideal technique for detecting this fluctuation. Currently, short-time Fourier Transform is the favored method but with its fixed time and frequency resolutions, it is known to suffer from spectral leakages that distort the measurements, especially if the signal is varying. This dissertation explores the use of Wavelet technique to overcome this deficiency.